Parcerias entre municípios paulistas e entidades privadas com fins lucrativos para a oferta de educação infantil: análise dos instrumentos jurídicos adotados - Azevedo, Caroline de Fátima Nascimento de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research aims to examine the legal instruments adopted by partnerships between private for-profit institutions and five municipalities in São Paulo State (Araras, Hortolândia, Limeira, Piracicaba and Sumaré) for the supply of vacancies in early childhood education. From intensive research carried out within the Group of Studies and Research in Educational Policy (Greppe), it was observed that these five counties have signed partnerships with private institutions for purpose of profit, which is beyond the traditional partnerships between Government and nonprofit institutions (community, religious or philanthropic). It was also noted that those municipalities use several instruments for the formation of partnerships: sometimes the term of an agreement, either the vesting term. Based on these studies and with this investigative clipping, the following objectives were set: (a) systematize the legal instruments used by the municipalities that were under investigation; (B) identify the main characteristics of these documents; and (c) verify whether such legal instruments meet the legal requirements and configure part of legislative strategies for the allocation of public resources in the private sphere. It is a qualitative research, with documentary nature. The methodological procedures used were document analysis, literature review and content analysis. Analyzing the legal instruments used by the municipalities of Hortolândia, Piracicaba and Sumaré (Term of Agreement) in conjunction with the constitutional and infra-constitutional legislations, it was concluded that they are riddled with illegality, since the law does not allow the transfer of public resources to private profit-making institutions to offer vacancies in early childhood education, albeit in the form of scholarships. As regards the legal instruments used by the municipalities of Araras and Limeira, although they received the jurisnomen of “vesting term”, it can be...

Este trabalho visa analisar os instrumentos jurídicos adotados por parcerias entre instituições privadas com fins lucrativos e cinco municípios do interior paulista (Araras, Hortolândia, Limeira, Piracicaba e Sumaré) para a oferta de vagas na educação infantil. Por meio de intensa pesquisa realizada no âmbito do Grupo de Estudos e Pesquisa em Política Educacional (Greppe), observou-se que esses cinco municípios firmaram parcerias com instituições privadas de finalidade lucrativa, o que foge às tradicionais práticas de formação de convênio entre Poder Público e instituições sem fins lucrativos (comunitárias, confessionais ou filantrópicas). Também foi apontado que os referidos municípios se utilizam de instrumentos jurídicos diversos para o estabelecimento das parcerias: ora o termo de convênio, ora o termo de concessão. Com base nesses estudos e com esse recorte investigativo, foram traçados os seguintes objetivos: (a) sistematizar os instrumentos jurídicos utilizados pelas prefeituras municipais que foram objeto da investigação; (b) identificar as principais características desses documentos; e (c) verificar se tais instrumentos jurídicos atendem às exigências legais, bem como se configuram parte de estratégias legislativas para alocação de recursos públicos na esfera privada. Trata-se de uma pesquisa qualitativa, de natureza documental. Os procedimentos metodológicos empregados foram a análise documental, a pesquisa bibliográfica e a análise de conteúdo. Analisando os instrumentos jurídicos utilizados pelos municípios de Hortolândia, Piracicaba e Sumaré (termo de convênio) em conjunto com as legislações constitucional e infraconstitucional, concluiu-se que eles estão eivados de ilegalidade, uma vez que a legislação não permite o repasse de recursos públicos a instituições privadas de finalidade lucrativa para a oferta de vagas na educação infantil, ainda que sob a forma de bolsas de...
Keywords: Education and state; Educação e Estado - São Paulo (Estado); Parceria público-privada; Educação de crianças; Instrumentos juridicos